PENINGKATAN KETERAMPILAN MENULIS TEKS PROSEDUR MELALUI MODEL DISCOVERY LEARNING BERBANTUAN MEDIA KAPROLA PADA SISWA KELAS II SEKOLAH DASAR - Muhammad Afdholil Kholiqoh Insani; Sigit Ariyanto; Muhammad Zakky Ali; Rani Setiawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve the writing skills of procedural texts of grade IIB students at SD 1 Wergu Wetan through the Discovery Learning model assisted by KAPROLA (Step-by-Step Procedure Cards) media. The study used the Classroom Action Research (CAR) model of Kemmis and McTaggart, conducted in two cycles, involving 20 students as research subjects. The results showed significant improvement, with the class average score increasing from 70.13 in Cycle I to 89.35 in Cycle II, and classical learning completion increasing from 15% to 100%. Improvements also occurred in all assessed writing skill indicators.